Quality properties of indonesian traditional terasi: a review - Askur Rahman; Retno Astuti; Sucipto Sucipto (AGROINTEK, 2023)
Terasi constitutes an Indonesian traditional fermented product made from shrimp or fish (or a mixture of both) at a high salt concentration with or without incorporating approved additional ingredients. With a distinct flavor and solid texture (paste), terasi is widely consumed as a seasoning ingredient, but it is still produced using a traditional method that lacks quality inspection. Quality properties of terasi, i.e., physical, chemical, and microbiological aspects, are essential since they highly affect consumer acceptance. This article reviews the quality profiles of terasi, covering such aspects as food safety, health, sensory, shelf life, and its use. The safety of biological, chemical, and physical threats can be used to evaluate the quality of terasi from a safety perspective. In addition, the nutritional content, functional qualities, and satiety characteristics of terasi indicate its quality from a health standpoint. Based on taste, texture, aroma, and color, the sensory qualities of terasi are evaluated to determine its quality. From the time the product is developed until consumers utilize it without any modifications, the quality of terasi based on the shelf life aspect is observed. The quality of terasi in terms of usability is determined by items that are user-friendly or, in other words, practical